Synthesis,Charaterization and Biological Activity Studies of Some Transtion and Non transition Metalcomplexes with(4 – Dithiocarbamato-N-(5- methylisoxazole-3-yle)- ion-ligand) - Numan, Ahmed Thabit; ulrazzaq, Salim Salah Abd (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This work involves the preparation of the ligand [KL] :-                    ÂÂÂÂÂÂK[4-(N-(5-methylisoxazol-3-yl) sulfamyl) phenylcarbamodithioate] from the reaction of sulfamethoxazole  with Carbon disulfide  in the presence of  potassium hydroxide under reflux (4 hours) using methanol as asolvent. The prepared ligand was characterized using FT-IR, UV-Vis, 1H,13Câ€“NMR spectroscopy, molar conductivity and melting point,  Complexes for the above ligand [KL] with some bivalent transition and non-transition metals (Mn +2, Co+2  , Ni+2  , Cu+2  , Cd+2  , Zn+2 , Cd+2   and Pd+2  ) were prepared. All prepared complexes were characterized by spectrophotometric methods such as FT-IR , UV-Vis, atomic absorbition ,magnetic sysceptibility, in addition chloride content , melting point and molar conductivity. All prepared complexes were found to have tetrahedral geometry except the (pd) complex was square planer. Biological activity for the ligand and some of its complexes were studied against two species of characterized Staphylococcus aureus"" and bacteria Escherichia Coil.